Avaliação da atividade farmacológica do extrato aquoso das cascas de Plathymenia reticulata Benth - ASSUNÇÃO, Ana Paula Ferreira (Universidade Federal do Oeste do Pará, 2021)
Plathymenia reticulata Benth is a medicinal plant used in the treatment of various diseases, especially by traditional communities of the Amazonian savannas in the municipality of Santarém, state of Pará - Brazil. The aim of this study was to evaluate the pharmacological activity and the effect of the aqueous extract of the bark of Plathymenia reticulata (EAPR) on behavior and learning in rats, as well as determine their phytochemistry. For this, the antimicrobial activity was verified by broth microdilution methods and through bactericidal and fungicidal minimum concentrations, the antinociceptive activity was assessed using the formalin test, antiedematogenic activity by the paw edema test induced by carrageenan and the Morris water maze, Y maze, open field, light/dark box and swivel bar tests were performed to evaluate the behavior and learning in rats. The phytochemical analysis was performed by thin layer chromatography. The EAPR showed promising activity against both gram-positive and gram-negative bacteria with minimum inhibitory concentration of 0.0008 mg/mL for Enterococcus faecalis and 0.0004 mg/mL of Klebsiella pneumonia, but was not efficient against Candida spp. The EAPR at a dose of 240 mg/kg inhibited in 100% the time of licking paws in the inflammatory phase of the formalin test. In the paw edema induced by carrageenan test, EAPR at a dose of 240 mg/kg decreased 82.41%, 80.95%, 81.87% and 86.90% of the volume of edema in 1st, 2nd, 3rd and 4th hour after administration of carrageenan. Regarding the assessment of the behavior and learning in mice, the extract showed no depressant activity on the CNS, as in the tests the animals showed no behavioral and no motor changes. The EAPR has tannins such as secondary metabolites. At the moment, it can be proposed that the EAPR has antimicrobial, antinociceptive and anti-inflammatory, which provides scientific basis for their ethnobotanical use properties. These activities can be attributed to the presence of phenols from the group of condensed tannins. However, it is important that further studies be conducted to understand the mechanisms involved in these pharmacological actions plus additional studies evaluating the effects of the extract on hematopoiesis, liver and kidney function for us to complete the safety profile of this species.